1984
DOI: 10.1007/bf01412541
|View full text |Cite
|
Sign up to set email alerts
|

Molecular compton profiles from inelastic atom-electron scattering

Abstract: Recent measurements of the electron loss peak from H~-ions impinging on Ar have been analyzed in terms of projectile Compton profiles (CP). It is shown that projected momentum distributions, i.e. CP's, can be determined for the molecular ion H~-.Recently it has been demonstrated that Compton profiles (CP), i.e. projected electron momentum distributions, of either target atoms or projectile ions can be obtained by inelastic ion-electron scattering [1]. It is the aim of this paper to show that existing data of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The (J(q))vlb for H: and D: , calculated using two sets of distribution factors (the FC and VBD), are given in table 1. Bell (1984) analysed the ELP (at an emission angle of 135"), reported by Kover et a1 (1983), in terms of CP at the incident energies of 0.8 and 1.995 MeV amu-' from Hl-Ar collisions. The obtained CP were shown (Bell 1984) to be independent of incident energies and targets.…”
Section: Vjmentioning
confidence: 99%
See 2 more Smart Citations
“…The (J(q))vlb for H: and D: , calculated using two sets of distribution factors (the FC and VBD), are given in table 1. Bell (1984) analysed the ELP (at an emission angle of 135"), reported by Kover et a1 (1983), in terms of CP at the incident energies of 0.8 and 1.995 MeV amu-' from Hl-Ar collisions. The obtained CP were shown (Bell 1984) to be independent of incident energies and targets.…”
Section: Vjmentioning
confidence: 99%
“…Bell (1984) analysed the ELP (at an emission angle of 135"), reported by Kover et a1 (1983), in terms of CP at the incident energies of 0.8 and 1.995 MeV amu-' from Hl-Ar collisions. The obtained CP were shown (Bell 1984) to be independent of incident energies and targets. This demonstrated that the PWLA is valid for this collision process at those incident energies.…”
Section: Vjmentioning
confidence: 99%
See 1 more Smart Citation